2018
DOI: 10.12659/msm.910054
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA DUXAP8 Enhances Renal Cell Carcinoma Progression via Downregulating miR-126

Abstract: BackgroundRenal cell carcinoma (RCC) is one of the common malignant tumors in the urinary system, which endangers human health for a long time. The past decade, the molecular biology of renal cell carcinoma has made considerable progress, so that we have a more profound understanding of renal cell carcinoma. Molecular biological mechanism of renal cell carcinoma remains to be explored. Evidence indicates that long non-coding RNAs (lncRNAs) may be important players in human cancer progression, including RCC. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…Increasing studies have shown that lncRNA can repress miRNAs as competitive endogenous RNAs (ceRNAs). It is reported that DUXAP8 can act as a ceRNA of miR‐577 to promote the expression of RAB14, thus promoting the migration and invasion of colorectal cancer cells ; in renal cell carcinoma, DUXAP8 targets miR‐126 and promotes cancer progression . Based on the difference in the expression and role of DUXAP8 and miR‐422a in HCC, we speculated that there was a regulatory relationship between them.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Increasing studies have shown that lncRNA can repress miRNAs as competitive endogenous RNAs (ceRNAs). It is reported that DUXAP8 can act as a ceRNA of miR‐577 to promote the expression of RAB14, thus promoting the migration and invasion of colorectal cancer cells ; in renal cell carcinoma, DUXAP8 targets miR‐126 and promotes cancer progression . Based on the difference in the expression and role of DUXAP8 and miR‐422a in HCC, we speculated that there was a regulatory relationship between them.…”
Section: Discussionmentioning
confidence: 97%
“…It is reported that DUXAP8 can act as a ceRNA of miR-577 to promote the expression of RAB14, thus promoting the migration and invasion of colorectal cancer cells 31 ; in renal cell carcinoma, DUXAP8 targets miR-126 and promotes cancer progression. 13 Based on the difference in the expression and role of DUXAP8 and miR-422a in HCC, we speculated that there was a regulatory relationship between them. We validated the binding relationship between DUXAP8 and miR-422a by dual-luciferase reporter gene assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas decrease expression of CADM1-AS1 [28], NBAT-1 [29,30], lnc-ZNF180-2 [31], NONHSAT123350 [32], downregulate RNA in androgen independent cells (DRAIC) [33], and EPB41L4A-AS2 [34] were related to poor prognosis ( Table 1). The newly discovered pseudogene-derived lncRNA named DUXAP8, a 2107bp RNA, was markedly upregulated in RCC [35]. Deciphering the molecular and biological mechanism(s) suggested that lncRNA DUXAP8 enhanced RCC progression through downregulating miR-126, which opens new prognostic approach for the treatment of RCC [35].…”
Section: Long Noncoding Rnas As Biomarker In Renal Cell Carcinomamentioning
confidence: 99%